Future perspectives in nanomaterials for environmental and medical applications - Abel Inobeme; Adetunji CO; Ajai AI (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2022)
Nanoscale materials are unique materials with outstanding properties when compared to their bulk counterparts hence their exploration, fabrication and applications have gained remarkable attention in various fields of human endeavors such as environment, medicine, and engineering, amongst others.